PENGARUH WORKPLACE STRETCHING EXERCISE TERHADAP KELUHAN MUSCULOSKELETAL DISORDERS PADA MAHASISWA KEPERAWATAN UNIVERSITAS UDAYANA PADA MASA PANDEMI COVID-19 - Hariani, Ni Wayan Deva Diah; Prapti, Ni Ketut Guru; Antari, Gusti Ayu Ary (Coping: Community of Publishing in Nursing; Vol 11 No 5 (2023): Oktober 2023DO - 10.24843/coping.2023.v11.i05.p06, 2023)
Musculoskeletal Disorders (MSDs) are a series of pain or discomfort that nursing students often complain about during online learning. One of the interventions that can reduce musculoskeletal complaints is Workplace Stretching Exercise (WSE). WSE is a series of active stretches that can be done at work. The purpose of this study was to determine the effect of WSE on MSDs. This research is a pre-experimental study with one group pre-test post-test only design. The sample in this study amounted to 28 students who are members of one group using purposive sampling technique. Musculoskeletal complaints were measured using the Nordic Body Map (NBM) questionnaire. The type of complaint before the intervention was most often experienced by students was the right shoulder 78,6%. After the intervention was given, the most frequent complaint was the upper neck 53,6%. The mean score of MSDs before and after the intervention decreased from 51,00 to 39,25. Data analysis using the Wilcoxon test statistical test at a significance level of 95% obtained p-value of 0,000. This shows that there is an effect of WSE on MSDs in nursing students at Udayana University.